2019
DOI: 10.3390/ijerph16183399
|View full text |Cite
|
Sign up to set email alerts
|

Leg Dominance as a Risk Factor for Lower-Limb Injuries in Downhill Skiers—A Pilot Study into Possible Mechanisms

Abstract: Leg dominance has been reported as one potential risk factor for lower-limb injuries in recreational downhill skiers. The current study proposed and tested two possible mechanisms for a leg dominance effect on skiing injuries—imbalance of the knee muscle strength and bilateral asymmetry in sensorimotor control. We hypothesized that the knee muscle strength (Hypothesis 1; H1) or postural control (Hypothesis 2; H2) would be affected by leg dominance. Fifteen well-experienced recreational downhill skiers (aged 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 47 publications
8
55
0
Order By: Relevance
“…Adolescents may control task-relevant movement components in a rather reliable way; however, redundant components show alterations leading to the observed variability. Results are further in line with previous studies investigating leg dominance [36,37,52], sensory perturbation [48], or dual tasking [39] and its effect on postural control, presenting some but not all PM k to be affected. Although adolescents are suggested to heavily rely on visual information [13], no differences could be observed between the eyes-open and eyes-closed trial.…”
Section: Main Results-motor Control Differences Between Adolescents Vsupporting
confidence: 91%
See 2 more Smart Citations
“…Adolescents may control task-relevant movement components in a rather reliable way; however, redundant components show alterations leading to the observed variability. Results are further in line with previous studies investigating leg dominance [36,37,52], sensory perturbation [48], or dual tasking [39] and its effect on postural control, presenting some but not all PM k to be affected. Although adolescents are suggested to heavily rely on visual information [13], no differences could be observed between the eyes-open and eyes-closed trial.…”
Section: Main Results-motor Control Differences Between Adolescents Vsupporting
confidence: 91%
“…If more N k are present, a tighter movement control can be suggested as the sensorimotor system makes more frequent corrections. Reductions in N k may be related to longer processing times for postural adjustments or could indicate that a movement component is not controlled as tightly, for example, because the control of PM k is deprioritized [36][37][38].…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…We argued that this implies divergent effects in different movement dimensions/components, depending on the relevance of the movement component for the task of maintaining stability. Specifically, we predicted for dual-tasking that anterior-posterior ankle sway, which is claimed to be of high importance for postural control [29,31,32] and was represented in PM 1 , would decrease in amplitude (aVar k ) while the frequency of control interventions (N k ) would increase [45][46][47]. Our results supported the first prediction (aVar 1 decreased), but did not confirm the second prediction (N 1 was not significantly different from eyes-open standing and the difference to N 1 in the eyes-closed trial is most likely an effect of the system coping with reduced sensory information in the eyes-closed trial [17]).…”
Section: Resultsmentioning
confidence: 99%
“…A decline in N k could be an indication that the processing time for adjustments increases, or it could be an indication that a movement component is not controlled as tightly, e.g., because the system attributes less priority to the movement component. A number of previous studies have already used this variable and found that it is sensitive, for example, to age differences or to leg dominance [45][46][47].…”
Section: Dependent Pm-based Variablesmentioning
confidence: 99%